2005
DOI: 10.1016/j.physb.2005.01.375
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of the metal–insulator transition in BaVS3

Abstract: A sequence of structural transitions occurring in the quasi-one-dimensional (1D) 3d 1 system BaVS 3 at low temperature was investigated by high resolution synchrotron X-ray diffraction. The orthorhombic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Beside previous electric transport, magnetization and spectroscopic studies, high-resolution specific heat and thermal conductivity measurements can give further insight into the nature of the electronic states and the dominant scattering mechanism. With lowering the temperature, BaVS 3 undergoes three continuous phase transitions; a second-order structural (hexagonalto-orthorhombic) phase transition at T S ∼ 250 K [17] followed by a metal-to-insulator transition (MIT) accompanied by a structural tetramerization [18] at T MI ∼ 69 K. The onset of a long range magnetic order takes place at T X ∼ 30 K in the form of an incommensurable antiferromagnetic ordering [19]. Our study shows that both the high temperature structural and the MIT is accompanied with anomalies in the specific heat, while the thermal conductivity only indicates the onset of the MIT (see Fig.…”
Section: Bavsmentioning
confidence: 99%
“…Beside previous electric transport, magnetization and spectroscopic studies, high-resolution specific heat and thermal conductivity measurements can give further insight into the nature of the electronic states and the dominant scattering mechanism. With lowering the temperature, BaVS 3 undergoes three continuous phase transitions; a second-order structural (hexagonalto-orthorhombic) phase transition at T S ∼ 250 K [17] followed by a metal-to-insulator transition (MIT) accompanied by a structural tetramerization [18] at T MI ∼ 69 K. The onset of a long range magnetic order takes place at T X ∼ 30 K in the form of an incommensurable antiferromagnetic ordering [19]. Our study shows that both the high temperature structural and the MIT is accompanied with anomalies in the specific heat, while the thermal conductivity only indicates the onset of the MIT (see Fig.…”
Section: Bavsmentioning
confidence: 99%
“…53 This provides a contrast to the 1D structure of RbVSe 2 which contains edge-sharing VSe 4 tetrahedra. 54 A detailed study 55 of the 1D phase BaVS 3 has shown that the metalinsulator transition in this 2H perovskite arises from a Peierl's distortion of the Fig. 5 The structure of the high pressure, superconducting phase of GaTa 4 Se 8 .…”
Section: Chalcogenidesmentioning
confidence: 99%